PENDIDIKAN ANEMIA GIZI MELALUI GAMES ULAR TANGGA MENINGKATKAN ASUPAN GIZI PADA REMAJA PUTRI - Panjaitan, Winda Sauci; Kusnandar, Kusnandar; Hikmayani, Nur Hafidha; Sudikno, Sudikno (Poltekkes Kemenkes Bandung, 2023)
One of the nutritional problems that often occurs among adolescents is iron deficiency anemia, especially for adolescent girls who have a higher risk of anemia than young men. Based on the prevalence in the world in adolescent girls reached 32.8%, meaning that there are still anemia problems that have not been resolved. The study aimed to determine the effect of nutritional anemia education through snakes and ladders games on nutritional intake in adolescent girls. The design used quasi-experiment with pre test-post test method with control group on 48 class X students at SMK Negeri 1 Banyudono. Nutrition education through snakes and ladders games was conducted once a week for 4 weeks, containing anemia definition material and food intake selection. Food intake data was obtained through the interview method using a 3x24 hour food recall questionnaire. The results showed that there was an effect of snakes and ladders games on iron (p=0.017) and protein (p<0.001) intake. Snakes and ladders games had no effect on folic acid (p=0.753) and vitamin C (p=0.886). There was an effect of lecture method on folic acid (p<0.001). There was no effect of lecture method on iron (p=0.081), protein (p=0.295) and vitamin C (p=0.230) intake. The conclusion shows that snakes and ladders games significantly affect iron and protein intake, while the lecture method significantly affects folic acid intake. Therefore, the application of nutrition education materials is carried out gradually and continuously to achieve positive behavioral changes and prevent health problems in daily life.